Effect of addition an amino acid or its combination with EDTA on DNA integrity and morphometry sperm heads of freeze-dried bovine spermatozoa - Said, S.; Maulana, T.; Setiorini, S.; Ibrahim, G.E.; Ramadhan, M.N.; Christopher, E. (Diponegoro University, 2020)
The objective of the current study was to investigate the effect of addition an amino acid or its combination with EDTA on DNA integrity and morphometry sperm heads of freeze-dried bovine spermatozoa. Spermatozoa were freeze-dried in medium with the addition of an amino acid glycine, cysteine, glutamine, or its combination with EDTA. Sperm head morphometry was identified at 400X magnification using Axio Vision(Zeiss Company, Germany), while for membrane plasma integrity (MPI) determined by calculation of the percentage of spermatozoa having intact plasma membrane by osmotic resistance test method and DNA integrity analysis using acridine orange staining. Sperm head had declined in size after the freeze-drying process, MPI of FD spermatozoa gradually increased significantly when FD solution was added with an amino acid solution (glycine, cysteine) and its combination with EDTA. DNA integrity of all freeze-dried spermatozoa treatments was remaining intact, no significantly different (P>0.01) among treatments. The present study concluded that the addition of an amino acid (glycine, cysteine) or its combination with EDTA could be reduced morphometric sperm heads and plasma membrane damage of freeze-dried bovine spermatozoa, however, DNA integrity of bovine sperm nucleus remaining intact after the freeze-drying process without addition both amino acids and EDTA.